Pengaruh Model Pembelajaran Student Teams Achievement Division (STAD) terhadap Motivasi dan Hasil Belajar Kognitif Siswa - Ariningsih, Ni Luh Tuti; Fitriani, Herdiyana; Safnowandi, Safnowandi (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
The Student Teams Achievement Division (STAD) learning model is all student learning activities to improve existing abilities or improve new abilities, both abilities in the aspects of knowledge, attitudes and skills. These learning activities are carried out in group activities, so that participants can learn from each other through exchanging thoughts, experiences and ideas. The aim of the research was to determine the effect of the Student Teams Achievement Division (STAD) learning model on the motivation and cognitive learning outcomes of class XI Science students at SMA Negeri 7 Mataram. This type of research is quasi-experimental using two classes, namely the experimental class and the control class. The research design is pretest-posttest control group design. The research results showed that the learning motivation of experimental class and control class students was in the high category. This can be seen from the average value of motivation results for the experimental class of 73.90% and the average value of motivation results for the control class of 72.45%. From this data it can be seen that the motivation results of the experimental class are higher than the control class. Meanwhile, students' cognitive learning outcomes were obtained by hypothesis testing, where p = 0.000 < 0.05 significance level, so the hypothesis was accepted, namely that there was an influence of the Student Teams Achievement Division (STAD) learning model on students' cognitive learning outcomes.